2014
DOI: 10.1007/s12015-014-9521-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Changes of Human Granulosa Cells Exposed to 5-Azacytidine and Addressed Toward Muscular Differentiation

Abstract: Converting adult cells from one cell type to another is a particularly interesting idea for regenerative medicine. Terminally differentiated cells can be induced to de-differentiate in vitro to become multipotent progenitors. In mammals these changes do not occur naturally, however exposing differentiated adult cells to synthetic molecules capable of selectively reverting cells from their lineage commitment to a more plastic state makes it possible to re-address their fate. Only scattered information are avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 43 publications
11
50
0
Order By: Relevance
“…They confirmed that specific chemical compounds can push cells to a transient less committed state, increasing cell plasticity for a relative short time-window, but sufficient to re-address an adult mature cell into another differentiated cell type (Harris et al, 2011;Pennarossa et al, 2013Pennarossa et al, , 2014Brevini et al, 2014;Mirakhori et al, 2015;Chandrakanthan et al, 2016).…”
Section: Epigenetic Conversion: An Alternative Erasing Of "Epigeneticmentioning
confidence: 93%
See 2 more Smart Citations
“…They confirmed that specific chemical compounds can push cells to a transient less committed state, increasing cell plasticity for a relative short time-window, but sufficient to re-address an adult mature cell into another differentiated cell type (Harris et al, 2011;Pennarossa et al, 2013Pennarossa et al, , 2014Brevini et al, 2014;Mirakhori et al, 2015;Chandrakanthan et al, 2016).…”
Section: Epigenetic Conversion: An Alternative Erasing Of "Epigeneticmentioning
confidence: 93%
“…It is interesting to consider that this condition was transient and reversible, and, if returned to their standard culture medium, cells reverted to their original phenotype. Expression of pluripotency related genes decreased gradually within a few days (Pennarossa et al, 2013Brevini et al, 2014).…”
Section: Epigenetic Conversion: An Alternative Erasing Of "Epigeneticmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, DNA methylation plays a fundamental role during both early embryonic development and cell lineage specification, causing silencing of large fraction of the genome and subsequent expression of gene essential for the maintenance of the differentiated and tissue-specific phenotype. Based on this, 5-azacytidine (5-aza-CR), a well-characterized DNMT inhibitor, was selected in order to remove the epigenetic “blocks” that are responsible for tissue specification [35, 7]. This drug is a chemical analog of cytosine, it can be incorporated into DNA and RNA, causing an increased effect in resting as well as in dividing cells, and it is known to be a direct inhibitor of methylation in newly synthesized DNA by blocking DNMT function [56].…”
Section: Reviewmentioning
confidence: 99%
“…Indeed, it has been demonstrated that malignant transformations as well as several disorders, such as autism, bipolar disorder, familial hypertrophic cardiomyopathy, schizophrenia, and syndromes, namely Prader-Willi, Angelman, Beckwith-Wiedemann, and Silver-Russell, are directly or indirectly caused by epigenetic alterations in form of mutation of DNA methylation or incorrect histone modifications [25]. In particular, DNA methyltransferase (DNMT) inhibiting nucleoside analogs, non-nucleoside analogs, and histone deacetylase (HDAC) inhibitors have been proposed as potential anti-cancer drugs.…”
Section: Introductionmentioning
confidence: 99%